2022
DOI: 10.3390/cancers14163958
|View full text |Cite
|
Sign up to set email alerts
|

Targets for Renal Carcinoma Growth Control Identified by Screening FOXD1 Cell Proliferation Pathways

Abstract: Clinical association studies suggest that FOXD1 is a determinant of patient outcome in clear cell renal cell carcinoma (ccRCC), and laboratory investigations have defined a role for this transcription factor in controlling the growth of tumors through regulation of the G2/M cell cycle transition. We hypothesized that the identification of pathways downstream of FOXD1 may define candidates for pharmacological modulation to suppress the G2/M transition in ccRCC. We developed an analysis pipeline that utilizes RN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…A recent study showed that SLBP is indeed involved in breast cancer development and that inhibition of SLBP expression would be a promising therapeutic target for breast cancer ( 64 ). Transmembrane Protein 167A (TMEM167A) is a protein associated with vesicle transport and secretion that regulates the transport of newly synthesized proteins from the ER-Golgi to the cell membrane or other organelles and is also required for glioma growth in human cell xenografts and Drosophila models, and interference with TMEM167A expression impedes a variety of tumor cell proliferation ( 65 , 66 ). Transmembrane Protein 67 (TMEM67) plays a role in the migration of centrioles to the apical membrane and the formation of primary cilia ( 67 ).…”
Section: Resultsmentioning
confidence: 99%
“…A recent study showed that SLBP is indeed involved in breast cancer development and that inhibition of SLBP expression would be a promising therapeutic target for breast cancer ( 64 ). Transmembrane Protein 167A (TMEM167A) is a protein associated with vesicle transport and secretion that regulates the transport of newly synthesized proteins from the ER-Golgi to the cell membrane or other organelles and is also required for glioma growth in human cell xenografts and Drosophila models, and interference with TMEM167A expression impedes a variety of tumor cell proliferation ( 65 , 66 ). Transmembrane Protein 67 (TMEM67) plays a role in the migration of centrioles to the apical membrane and the formation of primary cilia ( 67 ).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have also demonstrated that FOXA1 and FOXD1 are broadly involved in tumor development as well as mitochondrial metabolism. Silencing FOXA1 or FOXD1 in RCC inhibits tumor growth by inhibiting cell cycle progression [ 31 , 32 ]. Moreover, recent research has indicated that FOXA1 may participate in sunitinib resistance in RCC [ 33 ].…”
Section: Discussionmentioning
confidence: 99%